Al-Mu'amalah Al-Madiyah Rules relating to human relations and economic transactions in accordance with the guidance of Sharia - Mahyudin, Mahyudin; Tarigan, Azhari Akmal; Syahreza, Rahmi (CV. Rayyan Dwi Bharata, 2025)
This research discusses the rules in Islam relating to economic relations and transactions in accordance with sharia guidance. Islam establishes key principles in economics, such as honesty, transparency, fairness, and the prohibition of usury and fraudulent practices. These principles aim to create an economic system that is fair, ethical, and brings blessings to individuals and society. Verses of the Qur'an and hadith emphasize the importance of maintaining integrity in every transaction to avoid exploitation or economic inequality. The prohibition of usury, for example, aims to protect weaker parties from financial exploitation and ensure balance in the distribution of wealth. In addition, transparency and honesty in buying and selling are important factors in building trust between transacting parties. This research also shows that the application of sharia rules in economic transactions can improve social welfare and prevent harmful economic practices. By applying Islamic principles in economic transactions, Muslims can create a business environment that is more fair, transparent and ethical, and provides broad benefits to the entire community. Therefore, an in-depth understanding of sharia rules in economics is very important so that each individual can carry out their economic activities in accordance with Islamic teachings and get blessings in life.